Renal Pathology in Portuguese HIV-Infected Patients - Ferreira, AC (2011)
HIV-infected patients may be affected by a variety of renal disorders. Portugal has a high incidence of HIV2 infection and a low prevalence of HIV-infected patients under dialysis treatment. The aim of this study was to characterise the type of renal disease in Portuguese HIV-infected patients and to determine if HIV2 infection is associated to renal pathology. Only 60 of the 5158 HIV-infected patients followed in our hospital underwent renal biopsy. Clinical and laboratory data and the type of renal disease were reviewed. Male gender was predominant (76.7%), as was Caucasian race (78.3%). Mean age was 37.9±10.6 years. The majority had criteria for AIDS, 66% were on combined antiretroviral therapy and 18.3% were on dialysis. The predominant lesions were immunecomplex glomerulonephritis (n=19), tubulointerstitial nephropathy (n=12), focal segmental glomerulosclerosis(n=11), followed by HIVAN (n=8). Other patterns(amyloidosis, vasculitis, minimal change lesion) were observed. Only three patients were HIV2 infected, and presented diabetic nephropathy, acute tubular necrosis and tubulointerstitial nephritis. No correlations between clinical findings and renal pathology were found. In conclusion, renal disease in HIV patients has a broad spectrum, and renal biopsy remains the gold standard for establishing the diagnosis and guide treatment. Renal disease is not frequent in HIV2-infected patients, and, when present, is probably not directly associated with HIV infection.